Objective Signs of a Crime of Resistance to an Official or a Person Performing a Civil Duty - Abidov Akbar Abdulxayevich (International Journal on Orange Technologies, 2021)
The dissertation explores the general description and legal analysis of responsibility for resisting a government official or a person performing a civic duty. It includes the concept of resistance to a civil servant or a person performing a civil duty, the social necessity of responsibility for this offense and crime, administrative and criminal elements, aggravating circumstances for violating the rules, analysis of foreign legislation and proposals and scientific research. analysis, recommendations are described